2015
DOI: 10.1186/1756-8935-8-2
|View full text |Cite
|
Sign up to set email alerts
|

CENP-A nucleosomes localize to transcription factor hotspots and subtelomeric sites in human cancer cells

Abstract: BackgroundThe histone H3 variant CENP-A is normally tightly regulated to ensure only one centromere exists per chromosome. Native CENP-A is often found overexpressed in human cancer cells and a range of human tumors. Consequently, CENP-A misregulation is thought to contribute to genome instability in human cancers. However, the consequences of such overexpression have not been directly elucidated in human cancer cells.ResultsTo investigate native CENP-A overexpression, we sought to uncover CENP-A-associated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(174 citation statements)
references
References 81 publications
14
160
0
Order By: Relevance
“…CENP-A overexpression and misincorporation at non-centromeric loci is observed in many cancers, and serves as a potent prognostic marker in conjunction with other centromere genes [7578]. Inhibition of CENP-A amino terminal methylation and hyperphosphorylation of Ser18 by cyclin E1/CDK2 contributes to chromosome instability [11,12 •• ], suggesting that perturbations in posttranslational modifications of CENP-A may contribute to cancer phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…CENP-A overexpression and misincorporation at non-centromeric loci is observed in many cancers, and serves as a potent prognostic marker in conjunction with other centromere genes [7578]. Inhibition of CENP-A amino terminal methylation and hyperphosphorylation of Ser18 by cyclin E1/CDK2 contributes to chromosome instability [11,12 •• ], suggesting that perturbations in posttranslational modifications of CENP-A may contribute to cancer phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…It is equally unknown whether this up-regulation is limited to particular types of cancer or at what point it occurs during tumor evolution. Initial work in human cancer cell lines focusing on exogenously overexpressed CENP-A showed that it can mislocalize outside the centromere in euchromatin, which is equally the case for the endogenously up-regulated protein (Athwal et al 2015). Given how H3.1 and H3.3 oncohistones harboring K-to-M mutations contribute to cell type-specific tumors such as glioblastomas, chondroblastomas, and sarcomas (Schwartzentruber et al 2012;Sturm et al 2012;Fang et al 2016;Lu et al 2016), a tempting hypothesis could be that aberrant CENP-A expression might drive tumorigenesis in a cell type-specific manner.…”
mentioning
confidence: 99%
“…On the other hand, CENP-A overexpression is associated with its mislocalization outside the centromere to euchromatic regions in tumorigenesis (Allshire and Karpen 2008; Amato et al 2009; Athwal et al 2015; Filipescu et al 2017; Hu et al 2010; Lacoste et al 2014; Li et al 2011; Shrestha et al 2017; Tomonaga et al 2003; Wu et al 2012; Zhang et al 2016). Therefore, in normal conditions, there must exist a mechanism to eliminate CENP-A from non-centromeric loci.…”
Section: Diversity Of Cenp-a Modifications Across Speciesmentioning
confidence: 99%